(3HdhZ GdCQH HTQM TPhQ GdPgHs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa , GHf gTGe , LeGd GdOjf , CHh eMeO,J (B761 (3g` s ((3eMeO Hf CMeO GdObGb GdTgjQ (B- (3GdjeGfj s)
(3ChdgG (B:s
(3hHYO, aEf cJGH TPhQ GdPgH GHf gTGe hcGf ajg eG jMJGL Edi HjGf GdeQGO s
(3BNQgG (B:s
(3ef LgI PcQ JejjR KfJjf, hef LgI YOe eWGHbJg dgeG, hcGf Mbg EP ejR Cf jbhd(B: (3KfJG MfXdJjf s
(3HChdgG JedcGJ CbOegG SfI (B1107(3g`s
(3hHgG fXGe GdJYbjHI hocJHJ YHGQGJ GdCUd HGdMeQIs
(3hQOJ CjVkG JMJ Qbe(B502s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs